2011
DOI: 10.3109/13668250.2010.549464
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and health status in adults with intellectual disabilities: Results of the European POMONA II study

Abstract: Some evidence of health disparities was found for older people with ID, particularly in terms of underdiagnosed or inadequately managed preventable health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 68 publications
4
89
1
6
Order By: Relevance
“…Four of these articles 90,[102][103][104] reported findings from the same study and a further two articles 109,125 reported findings from the same study, leaving 58 studies (see Table 3) remaining for the final systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these articles 90,[102][103][104] reported findings from the same study and a further two articles 109,125 reported findings from the same study, leaving 58 studies (see Table 3) remaining for the final systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…36 Muchos de los problemas de salud de las personas mayores con TDI permanecen sin identificar, no sólo por ellos mismos sino también por sus familiares, por el personal que los atiende y por los profesionales sanitarios. 37 Asimismo, la presentación clínica de la demencia en la persona con TDI puede diferir de la de la población general, ya que los cambios de personalidad y de comportamiento aparecen más temprano en el curso de la enfermedad. Por otra parte, es muy probable que haya un elevado número de demencias no diagnosticadas en esta población debido a las dificultades para establecer un diagnóstico y en el acceso a los servicios de atención de salud.…”
Section: Envejecimientounclassified
“…Por último, se encontraron evidencias de disparidades de salud en las personas mayores con TDI, particularmente en términos de infradiagnóstico y de falta de medidas de prevención en salud. 37 En España, el proyecto Pomona II recogió una muestra de 111 sujetos con TDI, y los datos obtenidos se compararon con los de la población general. La muestra con TDI presentó más casos de epilepsia, obesidad y dolor bucal, así como una elevada presencia de problemas sensoriales, de movilidad y psicosis.…”
Section: Proyecto Pomona IIunclassified
“…28 Besides presenting more severe levels of IDD, mental health issues and behaviour disorders, the population living in institutions has a higher mean age than their peers living in family households, and often leads a more sedentary life. 26,29 All these studies reflect the influence of variables like the severity of the IDD, ageing and institutionalization on the health status. This paper analyses the data from the survey EDAD 2008 carried out in order to understand the relationship of these variables with health profiles of people with IDD living in Spain.…”
Section: Health In Intellectual Developmental Disordersmentioning
confidence: 99%